Rapid Disappearance of Penumbra-Like Features near a Flaring Polarity Inversion Line: The Hinode Observations - B. Ravindra; Sanjay Gosain (Advances in Astronomy)
We present the observations of penumbra-like features (PLFs) near a polarity inversion line (PIL) of flaring region. The PIL is located at the moat boundary of active region (NOAA 10960). The PLFs appear similar to sunspot penumbrae in morphology but occupy small area, about 6×107 km2, and are not associated with sunspot or pore. We observed a rapid disappearance of the PLFs after a C1.7 class flare, which occurred close to the PIL. The local correlation tracking (LCT) of these features shows presence of horizontal flows directed away from the end-points of the PLFs, similar to the radial outward flow found around regular sunspots, which is also known as the moat flow. Hard X-ray emission, coincident with the location of the PLFs, is found in RHESSI observations, suggesting a spatial correlation between the occurrence of the flare and decay of the PLFs. Vector magnetic field derived from the observations obtained by Hinode spectropolarimeter SOT/SP instrument, before and after the flare, shows a significant change in the horizontal as well as the vertical component of the field, after the flare. The weakening of both the components of the magnetic field in the flare interval suggests that rapid cancellation and/or submergence of the magnetic field in PLFs occurred during the flare interval.